Nghiên cứu thành phần hóa học của cây mộc ký ngũ hùng (Dendrophtoe pentandra (L.) Miq., họ chùm gửi (Loranthaceae) ký sinh trên cây na Annona squamosa - Hào, Nguyễn Công; Khoa, Nguyễn Cửu; Kính, Chu Đình; Hùng, Mai Anh (Vietnam Journal of Chemistry, 2012)
Kaempferol 3-O-a-L-rhamnopyranoside, quercitrin, daucosterol and hesperidin were isolated from leaves and stem of Dendrophtaoe pentandra, which is a parasitic plant on Annona squamosa in Dong Nai of Vietnam. Their structures were determined by means of  ESI-MS,       1H-NMR,  13C-NMR and DEPT spectra.